Procurement in a Globalized Market : Optimizing Supplier Selection and Negotiations Processes While Managing Cultural Differences - Gerashchenko, Irina; Semenenko, Vadim; Procházka, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis addresses approaches to optimising supplier selection and contract negotiation processes in cross-cultural interactions. The study analyses existing procurement techniques and strategies, assesses the impact of cultural differences on the negotiation process, and proposes a universal model for improving the effectiveness of cross-cultural negotiations with suppliers. The methodological basis comprises interviews with procurement experts and an analysis of four practical cases that illustrate real-world challenges, including incomplete requirements, internal bias, cultural differences, the need to integrate global and local suppliers, and the impact of sustainable development on procurement decisions. The paper proposes a universal framework model for negotiations that combines strategic procurement practices and intercultural awareness. The study provides practical recommendations for companies looking into the improvement of procurement efficiency in a global and culturally diverse business environment.
Vedoucí práce: Vadim Semenenko
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses